Comparison of predicted and impedance determined growth of Listeria innocua in complex food matrices. (May 2020) - Nyhan, Laura; Johnson, Nicholas; Begley, Máire; O'Leary, Padraic; Callanan, Michael
Abstract: Indirect impedance has been used for the detection and enumeration of bacteria, however there is limited data regarding the ability of the method to measure growth and inhibition of microorganisms in food in response to preservatives. The aim of this study was to evaluate the suitability of the technique to determine maximum growth rates of Listeria innocua (used as a surrogate for Listeria monocytogenes ) in complex food matrices to which multiple preservative factors had been applied and assess the suitability of the data for use in predictive microbiology. Growth of L . innocua in laboratory medium (BHI broth) and two food matrices (zucchini purée and béarnaise sauce) under varying conditions of pH (5 & 5.3), water activity (0.93, 0.96 & 0.98) and acetic and propionic acid concentration (0, 1 & 2 mM) was monitored by the conductimetric Rapid Automated Bacterial Impedance Technology (R.A.B.I.T) system by means of CO2 emission for up to 120 h. Growth rates of L. innocua were determined for several conditions across the three test matrices and a good correlation between detection times and initial inoculum level was observed in most cases (R 2 ≥ 0.82). However, growth of L. innocua was not detected in a large number of conditions and comparison of growth rates determined by indirect impedance to those determined by plate counts indicated that in general, the R.A.B.I.T. system under-estimated growth. This study demonstrates that there are limitations associated with the technology, and as a result the system may be unsuitable for measuring microbial growth rates in complex food matrices under the environmental conditions tested and within the time duration of the study. Highlights: Evaluated impedance for measuring growth of Listeria in multi-hurdle food systems. Good correlation between Time To Detection and initial inoculum (R 2 ≥ 0.82). Impedance generally under-estimated growth when compared to plate counts. Growth of L. innocua not detected in several conditions. Impedance not suitable for studying growth/inhibition in food with multiple preservatives.